1 Addressing intimate partner violence: implications for medical curricula in mozambique. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Manuel, Beatriz; Roelens, Kristien; Valcke, Martin; Tiago, Armindo; Keygnaert, Ines
Abstract : Objectives: To identify ways to improve curricula on IPV mitigation-content in order to enhance prevention and medical care in Mozambique. Method: A review of the literature published between 1998 and 2018, evaluating the attention paid to IPV related content in medical curricula. A survey administered to third and 6th-year medical students (N387), enrolled in five medical schools in Mozambique focused on mapping in a comprehensive way students' perceived mastery of their knowledge, skills, and attitudes related to IPV competences. We screened Curricula of Mozambican medical schools on IPV. A number of video-vignettes represented real clinical scenarios are being developed in order to cover specific IPV knowledge, skills and attitudes as found in our previous studies. An adapted classroom-based interdisciplinary module of IPV is being developed and will be tested for the same medical students from our previous studies. This module is going to be evaluated using pre-post professional development by the means of a questionnaire on competences acquired. Results: IPV content is hardly and inconsistently addressed when focusing on the related content and instructional strategies being adopted. Conclusions: There is a need for a more comprehensive approach to developing medical student's knowledge, skills, and attitudes to deal with the survivors of IPV.